Maternal and neonatal risk factors for early-onset group B streptococcal disease: a case control study - Al-Kadri HM; Bamuhair SS; Al Johani SM; Al-Buriki NA; Tamim HM (Dove Medical Press, 2013)
Hanan M Al-Kadri,1 Samira S Bamuhair,2 Sameera M Al Johani,3 Namsha A Al-Buriki,1 Hani M Tamim4 1Department of Obstetrics and Gynecology, 2Department of Basic Medical Sciences, 3Microbiology Division, 4Department of Medical Education, College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, King Abdulaziz Medical City, Riyadh, Kingdom of Saudi Arabia Objectives: To identify the prominent maternal and neonatal risk factors associated with early-onset group B streptococcus (EOGBS) disease in neonates and to determine their importance by comparing them with a control group. Setting: Neonatal unit at King Abdulaziz Medical City, Riyadh, Kingdom of Saudi Arabia. Patients: Cases were infants <7 days of age with invasive group B streptococcus (GBS) disease diagnosed between January 1, 2000 and December 31, 2009. Controls were healthy infants born in the same hospital during the same period having the same birth weight and gestational age category. Main outcome measures: Maternal risk factors for developing EOGBS disease, feto–maternal and neonatal clinical data, their morbidities, mortalities, and length of hospital stay. Results: A total of 99 cases and 200 controls were included. The majority of cases presented in the first 72 hours of life (62/99 [63.9%]), of which 87/99 (89.7%) had at least one clinical risk factor for the development of EOGBS disease. Mothers of neonates with EOGBS disease were more likely to have GBS bacteriuria (odds ratio [OR] 10.76, 95% confidence interval [CI] 1.24–93.42), infection in the peripartum period (OR 8.92, CI 2.87–27.68), and temperature ≥38°C (OR 7.10, CI 2.50–20.17). GBS disease was associated with premature rupture of membranes and fetal tachycardia (P<0.01 for both). Neonates with EOGBS disease were more likely to have respiratory distress disease and convulsions, require tube feeding, and have longer hospital stays compared with the controls (P<0.01 for all). Stepwise multiple logistic regression has identified three risk factors that were associated with the highest tendency for the development of EOGBS disease. These were lack of antenatal attendance (OR =0.30 and CI 0.98–0.88), rupture of membranes (OR =9.62 and CI 3.1–29.4), and antibiotic use in labor (OR =0.16 and CI 0.38–0.67). Conclusion: A number of maternal risk factors were significantly associated with EOGBS disease. Taking these factors into consideration may result in preventing the occurrence of EOGBS disease, improve maternal and neonatal medical care, decrease their hospital stay, and reduce unnecessary hospital resource utilization. Keywords: group B streptococcus, neonatal morbidity, maternal morbidity, antenatal screening